Representações sociais de nutricionistas do núcleo ampliado de saúde da família sobre educação alimentar e nutricional - Natália de Alvarenga Guedes (2019)
Among the health promotion actions developed in PHC in Brazil are those related to food and nutritional education (EAN) carried out by nutritionists from the Expanded Nucleus of Family Health and Basic Care (NASF-AB). In order to unify the concept of EAN, promote reflection and orientation of the practice, and direct actions in the areas of health, education and assistance, for the use of active and problematizing educational resources and approaches, promoting a common field of reflection and orientation of the EAN practice, the Food and Nutrition Education Reference Framework for Public Policies was proposed in 2012, but despite the Framework, studies show that EAN practices have biomedical roots and operate with the transmission of knowledge, indicating that the mode of performing the EAN did not change. The practice of professionals, the way they think and act, is influenced by psychosocial and cultural experiences. Understanding the professionals' knowledge, attitudes and behaviors implies knowing the representations they have of the objects and ends that they aim to achieve, and indicates the importance of studying in more detail the social representations of those who perform them, including attitudes, behaviors and choices in different domains. Analysis of NASF-AB nutritionists' representations of EAN may help in understanding the implementation of their educational practices, and will allow us to find evidence to explain why the practices have not yet adapted to the Framework of Reference guidelines. Objective: To analyze the social representations of nutritionists of the NASF-AB on EAN. Methodology: This was a descriptive study, based on the Social Representations Theory (TRS), delineated with a qualitative method of research, carried out with 31 nutritionists at NASF-AB, Belo Horizonte City Hall, based on interviews and semi-structured questionnaire. To determine the sample size, we used stratified random probabilistic sampling with a 90% confidence interval. We analyzed the variables of the questionnaires with frequency distribution, and the interview data from the content analysis. Results: social representations of the interviews were collected, grouping them into four categories: EAN is to teach, educate and guide to healthy eating; EAN is to change habits, practices and behavior; EAN is to generate autonomy; EAN is to experiment and exchange experiences. The first two categories 10 have social representations anchored in the biomedical health paradigm, with social representations of normative NANs for privileging the transmission of information about nutritional characteristics of foods and for relating the modification of behaviors and eating habits to nutritional reeducation. The social representations of the other categories are anchored in the biopsychosocial paradigm, taking into account the social, cultural and subjective characteristics of the participants in the educational processes. However, the approach to certain subjects from the perspective of the professional to the detriment of the participant also refers to the biomedical paradigm in health. In both social representations with a biopsychosocial character, it is observed the coexistence in the practice of these professionals of two rationalities that are based on distinct and often antagonistic epistemological matrices, which may reveal an attempt to break with the hegemonic models of education in health, opposing the dominant tendency to develop educational practices that constitute specific modes of subjectivation based on the normativity and the homogenization of the participants. In this way, it is interpreted that the investment in an education through the way of the sensible and the experimentation, stems in this study much more of the intention to break with a dominant model admittedly fragile in terms of the production of answers, than of an understanding of education within another theoretical framework according to which learning takes place by the decipherment of signs. Final considerations: this research is expected to contribute to reflections on how EAN is performed in NASF-AB, and to allow discussions of EAN practices that privilege experimentation, awakening and sharpening senses. Experimentation calls for the invention of new modes of subjectivation and, consequently, the production of knowledge.